Albumin and Uptake of Drugs in Cells: Additional Validation Exercises of a Recently Published Equation that Quantifies the Albumin‐Facilitated Uptake Mechanism(s) in Physiologically Based Pharmacokinetic and Pharmacodynamic Modeling Research. Issue 12 (12th October 2015) - Poulin, Patrick; Haddad, Sami
Abstract : The impact of albumin concentration on the uptake of drugs in cells might involve mechanisms going beyond the free drug concentration hypothesis. Proceeding from the assumption that both the unbound and protein‐bound drug fractions can be available for uptake, several authors have argued that the uptake of highly bound drugs in cells might be driven mainly by the albumin‐facilitated uptake mechanism(s). Hence, a novel approach quantifying the additional contribution of the protein‐bound drug complex and pH gradient effect in diverse in vitro ‐to‐ in vi vo extrapolation (IVIVE) procedures of drug uptake and clearance has been proposed and extensively validated by Poulin et al. (2015. J Pharm Sci. Epub ahead of print); this approach consisted of replacing the unbound fraction in plasma (fup ) with an adjusted fup value (fup‐adjusted ). After a second review of literature, the objective of the present study was to perform further validation exercises of the concept of fup‐adjusted by using additional case examples of IVIVEs that covered diverse drug properties and experimental settings with varied albumin concentrations (e.g., perfused liver, isolated and suspended hepatocytes, and cultured cells overexpressing transporters). Again, the novel IVIVE method based on fup‐adjusted was the best‐performing prediction method of the uptake rate (or clearance) as a function of protein binding compared with the conventional method based on the fup theory (absolute average fold error of 1.4 vs. 7.4). Therefore, the present study confirms the utility of fup‐adjusted compared with fup in IVIVE procedures for drugs highly bound to albumin, and the improvement was observed particularly in the higher range of albumin concentrations. From these findings, we may conclude that uptake of these drugs in cells is primarily driven by the albumin‐bound form. Consequently, it is suggested to estimate the uptake kinetic parameters with cell‐based assays incubated in 100% human serum or to make a correction while the experimental data are generated either without albumin or with varied albumin concentrations, in order to predict more accurately the in vivo conditions in physiologically‐based pharmacokinetic and pharmacodynamic (PBPK/PD) modeling research. Overall, the protein‐facilitated uptake mechanism(s) could be another paradigm shift in addition to a previous paradigm related to the pH gradient effect. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:4448–4458, 2015